Does Intravenous Fentanyl Affect Apgar Scores and Umbilical Vessel Blood Gas Parameters in Cesarean Section Under General Anesthesia? - Maziyar Maghsoudloo; Negar Eftekhar; Mohammad Ali Noyan Ashraf; Zahid Husain Khan; Homeira Peiravy Sereshkeh (Acta Medica Iranica, 2011)
The administration of opioids during induction of general anesthesia is a matter of challenge in obstetric anesthesia. The aim of this study was to investigate the effects of intravenous fentanyl before induction of general anesthesia on the"1st and 5th minutes' Apgar scores" in neonates with elective cesarean surgery. In a double blinded randomized clinical trial on 60 parturients undergoing elective cesarean surgeries under general anesthesia in Vali-e-Asr Hospital, in Tehran, Iran, were divided randomly into two groups; the intervention group and the control. In intervention group, intravenous fentanyl 1µg/kg was administrated three minutes before anesthesia induction. The induction route, laryngoscopy and tracheal intubation were the same in the groups. The blood pressure (BP) and heart rate (HR) measures were recorded before anesthesia induction (as baseline measures) and so during laryngoscopy and intubation. The 1st and 5th minute's apgar scores and the pH of umbilical cord arterial and venous samples were compared in two groups. The systolic and diastolic blood pressure, mean arterial pressure and heart rate changes before and after induction and in various times after intubation showed significant difference between two groups (P0.05). Based on the results of this study, the administration of 1 µg/Kg intravenous Fentanyl, three minutes before induction of anesthesia for cesarean section can lead to a stable hemodynamic situation in mother and showed no effects on neonate`s outcomes. Fentanyl showed no effects on Apgar scores and on umbilical cord arterial and venous blood gases analysis and it probably can be used safely in elective cesarean surgeries. More studies are required to obtain a clear view.